Analysis of nonlinear conductivity of point contacts on the base of FeSe in the normal and superconducting state - Naidyuk, Yu.G.; Gamayunova, N.V.; Kvitnitskaya, O.E.; Fuchs, G.; Chareev, D.A.; Vasiliev, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Nonlinear conductivity of point contacts (PCs) on the base of FeSe single crystals has been investigated. Measured dV/dI dependencies demonstrate the prevailing contribution to the PC conductivity caused by the degraded surface. Superconducting (SC) feature in dV/dI like a sharp zero-bias minimum develops for relatively low ohmic PCs, where the deep areas of FeSe are involved. Analysis of dV/dI has shown that the origin of the zero-bias minimum is connected with the Maxwell part of the PC resistance, what masks energy dependent spectral peculiarities. Even so, we have found the specific features in dV/dI — the sharp side maxima, which may have connection to the SC gap, since their position follows the BCS temperature dependence. Exploring the dV/dI spectra of the rare occurrence with Andreev-like structure, the two gaps with Δ = 2.5 and 3.5 meV were identified.